A Simple Multistep Solution for Model Predictive Control in Multiphase Electric Drives. - González Prieto, Ignacio; Durán-Martínez, Mario Javier; González Prieto, Ángel; Aciego, Juan J. (IEEE Xplore, 2023)
The multiphase electric drive field of research is rather young, and most of the efforts in this area have been focused on appropriately extending different techniques that were already popular in three-phase systems. This is the case of finite-control set model predictive control (FCS-MPC), which has been a hot topic since 2009. Despite the numerous contributions on FCS-MPC for multiphase systems, all of them assume a single-step horizon in the predictions. This article shows the first attempt to include multistep predictions within the FCS-MPC that performs the current regulation. The extension from the three-phase case is not direct at all because the number of voltage vectors and subspaces is higher, this adding further complexity and eventually leading to issues related to the secondary current regulation. A smart selection of different subsets of voltage vectors is used to ease the implementation, and a modified cost function is developed to jeopardize the high instantaneous voltage values that significantly worsens the current quality at steady state. Experimental results confirm that the use of multistep FCS-MPC is feasible in multiphase electric drives, showing at the same time that some measures must be taken to minimize the distortion in the low-impedance secondary subspaces.
Keywords: Ingeniería eléctrica; Model predictive control; Multiphase electric drives; Multistep